How digital immigrants differ from digital native teachers in implementing technology in the classroom - Umi; Rizka Ramadhani (Teaching English as a Foreign Language Journal, 2022)
Learning culture in recent years has shown that we are following the 21-century learning system where technology has a crucial role in it. Technology implementation in the learning activity depends on the teachers' digital competence: digital immigrant and digital native teachers. This study investigated how technology is used by English teachers, focusing on the differentiating factor in implementing technology of two different generations.  This descriptive qualitative study involved English teachers from different generations; a teacher with 7 years of teaching experience and another with 22 years teaching experience. An in-depth semi-structured interview was conducted to collect the data. The Apple Classroom Tomorrow (ACOT) framework was used to analyze how the digital immigrant and digital native teachers in the classroom implement technology. The results are that the digital natives and immigrants differ in implementing technology because of age and experience, student motivation, and ICT facility. Generation Z is a participant in the EFL teaching-learning process in the digital age, and this study demonstrates that the digital competence of the teachers must be developed in order to meet their needs.